Intensified inequities: Young people's experiences of Covid‐19 and school closures in Uganda. (5th September 2022) - Datzberger, Simone; Parkes, Jenny; Bhatia, Amiya; Nagawa, Rehema; Kasidi, Joan Ritar; Musenze, Brian Junior; Naker, Dipak; Devries, Karen
Abstract: Uganda had the longest period of school closures worldwide as a response measure during the Covid‐19 pandemic. Drawing on longitudinal qualitative data from the Contexts of Violence in Adolescence Cohort Study (CoVAC) (2018–2023), we examine how this has affected the lives of adolescents in Uganda. Our analysis showcases how intersecting inequities based on socioeconomic circumstances, gender and location have intensified, with detrimental effects on young people's educational paths and life circumstances. Strategies that take the intersections of these inequities into account are urgently needed to help the most disadvantaged and marginalized young people return to school.